Functional safety and reliability for innovative vehicle braking system and integration with electric traction units. Issue 1 (February 2021) - Favilli, T.; Delogu, M.; Pugi, L.; Berzi, L.
Abstract: Newly electric vehicle architectures require intensive virtual and physical testing for safety assessment, due to the increasing relevance of By-Wire systems and the presence of innovative control algorithms for ordinary driving scenario, potential emergency situations or Advanced Driver-Assistance Systems implementation purpose. To reduce the development time while increasing system reliability and the a priori knowledge about its safety requirements, the evaluation of such aspects should be performed. In accordance to ISO26262 standard, authors propose a systematic approach based on Virtual FMEA, in order to assess the functional safety level of hybrid brake plant. Plant modification and securing strategy as been presented and implemented in target vehicle model, evaluating their performances in simulation environments, in order to met required Automotive Safety Integrity Level. This work is developed in the ambit of OBELICS European Project.